2022
DOI: 10.3389/fpsyt.2022.905332
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specific Sleep Parameters Among People With Substance Use Disorder

Abstract: IntroductionSleep can have substantial impacts in substance use disorder (SUD) pathogenesis, treatment, and recovery. Sex differences exist in both sleep and SUD, but how sleep is uniquely associated with SUD by sex is not known. The study objective was to compare, within sex, sleep parameters between individuals with SUD and non-substance misusing controls.MethodsSecondary analyses of a parent cross-sectional study examining the feasibility and acceptability of a novel neurocognitive phenotyping assessment ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Importantly, the relationship between sleep disturbance and OUD outcomes may differ by sex, and although OUD remains more prevalent among men, this gap by sex is rapidly closing ( 9 ). Specifically, sleep disorders, especially insomnia, are more prevalent among women than men, and one meta-analysis found that females had a risk ratio of 1.41 of insomnia compared to men ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the relationship between sleep disturbance and OUD outcomes may differ by sex, and although OUD remains more prevalent among men, this gap by sex is rapidly closing ( 9 ). Specifically, sleep disorders, especially insomnia, are more prevalent among women than men, and one meta-analysis found that females had a risk ratio of 1.41 of insomnia compared to men ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proposed underlying mechanisms for this sleep disparity are numerous, ranging from the role of sex-specific hormones to the impact of gendered social factors that more commonly affect women ( 11 , 12 ). Therefore, the relationship between sleep and OUD is likely multifaceted with interactions with sex and other biopsychosocial factors ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%